2004
DOI: 10.1007/s00221-003-1743-7
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness and postural stability in adults with Down syndrome

Abstract: The purpose of this study was to characterize postural sway in quiet standing under eyes-open and eyes-closed conditions, and to obtain a measure of postural stiffness during quiet standing in adults with Down syndrome (DS) versus control subjects. We obtained descriptive measures from centre-of-pressure (COP) data and analysed and compared COP trajectories and postural stiffness estimates from two stochastic models, the "pinned polymer" (PP) and "inverted pendulum" (IP) models. These estimates were correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
62
0
12

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 13 publications
10
62
0
12
Order By: Relevance
“…Much of this developmental delay continues to be attributed to isolated factors such as low muscle tone (Harris, 1985). Yet, recent research indicates that muscle tone evaluated under passive conditions may have little relationship with the strategies used by the nervous system under more dynamic conditions such as during standing (Webber, Virji-Babul et al 2004). In fact, Latash (2000) has suggested that over time, individuals with Down syndrome learn to develop adaptive motor strategies that optimise safety and stability.…”
Section: Introductionmentioning
confidence: 99%
“…Much of this developmental delay continues to be attributed to isolated factors such as low muscle tone (Harris, 1985). Yet, recent research indicates that muscle tone evaluated under passive conditions may have little relationship with the strategies used by the nervous system under more dynamic conditions such as during standing (Webber, Virji-Babul et al 2004). In fact, Latash (2000) has suggested that over time, individuals with Down syndrome learn to develop adaptive motor strategies that optimise safety and stability.…”
Section: Introductionmentioning
confidence: 99%
“…Repeated room mobile exposure of babies (illusory) led to a more coherent and stable coupling between visual information and the body oscillation (Polastri e Barela, 2005). Reduced stiffness over the trials during maintenance of static posture signaled the ability of adults to vary its stiffness with practice (Webber et al, 2004). Similarly Smith et al, (2007) observed the reduction of muscle stiffness values in tweens with SD after treadmill training, although the kinematic patterns adopted before and training have deferred of the control group patterns.…”
Section: Sensory Contribution To Postural Controlmentioning
confidence: 95%
“…Exists therefore an inconsistency between the clinical evaluation of tone in this population and the abovementioned findings remain the relationship between hypotonia and co-contraction little understood. For Webber et al, (2004) and Vuillerme et al, (2001) evaluation of tone about passive conditions can provide limited information about the strategies used by SNC. Among the explanations for the postural deficits found in individuals with DS, the favored explanatory hypothesis is that of a compromised sensorimotor system (Carvalho & Almeida 2009).…”
Section: Adaptive Choicementioning
confidence: 99%
“…Otyłość, a w konsekwencji częste występowanie płaskostopia u dzieci i młodzieży z DS [9] oraz nierzadko pojawiające się dysfunkcje wzroku i słuchu mogą być przyczyną zaburzeń kontroli równowagi ciała [10]. Badania kontroli rów-nowagi przeprowadzone przez innych autorów wskazują, że osoby z DS mają problemy z normalną kontrolą równowagi ciała [11,12]. Cabeza-Ruiz i wsp.…”
Section: Introductionunclassified